Activation of the inducible form of nitric oxide synthase in the brains of patients with multiple sclerosis. - Bagasra, O (1995)
Nitric oxide (NO) has been implicated as a pathogenic mediator in a variety of central nervous system (CNS) disease states, including the animal model of multiple sclerosis (MS) and experimental allergic encephalomyelitis. We have examined post-mortem brain tissues collected from patients previously diagnosed with MS, as well as tissues collected from the brains of patients dying without neuropathies. Both Northern blot analysis and reverse transcriptase (RT)-driven in situ PCR (RT-in situ PCR) studies demonstrated that inducible NO synthase (iNOS) mRNA was present in the brain tissues from MS patients but was absent in equivalent tissues from normal controls. We have also performed experiments identifying the cell type responsible for iNOS expression by RT-in situ PCR in combination with immunohistochemistry. Concomitantly, we analyzed the tissues for the presence of the NO reaction product nitrotyrosine to demonstrate the presence of a protein nitrosylation adduct. We report here that iNOS mRNA was detectable in the brains of 100% of the CNS tissues from seven MS patients examined but in none of the three normal brains. RT-in situ PCR experiments also demonstrated the presence of iNOS mRNA in the cytoplasm of cells that also expressed the ligand recognized by the Ricinus communis agglutinin 1 (RCA-1), a monocyte/macrophage lineage marker. Additionally, specific labeling of cells was observed when brain tissues from MS patients were exposed to antisera reactive with nitrotyrosine residues but was significantly less plentiful in brain tissue from patients without CNS disease. These results demonstrate that iNOS, one of the enzymes responsible for the production of NO, is expressed at significant levels in the brains of patients with MS and may contribute to the pathology associated with the disease.